Geology - Distribution of Uranium and Thorium in Precambrian Rocks of the Southwestern United States - David A. Sterling; Roger C. Malan (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1971)
The Atomic Energy Commission is investigating the distribution of uranium and thorium in the Precambrian of the western United States and the relationship of time-space-facies patterns of uranium and thorium enrichment in the Precambrian, to the major resources of umanium in Mesozoic and Cenozoic continental clastic sediments. The results of preliminary studies in the southwestern. United States are summarized. Approximately 50% of the uranium resource of the Free World is in deposits of Precambrian age, principally in lower Proterozoic conglomerates in Canada and South Africa (Uranium Resources, Joint Report, ENEA and IAEA, 1967). Most of the uranium resource of the United States is in Mesozoic and Cenozoic continental clastic sedimentary rocks that fill intracratonic basins. The Atomic Energy Commission (AEC) is investigating the distribution of uranium and thorium in the Precambrian of the western United States and the relationship of time-space-facies patterns of uranium and thorium enrichment in the Precambrian to the major resources of uranium in the Mesozoic and Ce-nozoic host sedimentary rocks. This paper summarizes the results of preliminary studies of the Precambrian in the southwestern United States including New Mexico, Arizona, southern Nevada, and southern California (Fig. 1). The host rock provenances for the major uranium resources in epigenetic deposits of Mesozoic and Ce-nozoic age in the western United States were in areas of extensive Precambrian exposure along the eastern margin of the Phanerozoic geosynclinal belt (Fig. 2). Mesozoic continental clastic sediments in the Colorado Plateau contain about two-thirds of the uranium resource of the United States. These sediments formed from detritus derived from the Mogollon highland in the southwestern United States where the Precambrian was extensively exposed1-1 (Fig. 2). A genetic relationship may exist between this provenance and the major uranium deposits of the Colorado Plateau. The Pre- cambrian might be equally important in the genesis of uranium deposits whether the most important process in the formation of these deposits was the leaching of low-order intrinsic amounts of uranium from Precam-brian granite or from Mesozoic pyroclastics derived from syntexis of the Precambrian basement rocks.' Precambrian Geochronology of the Southwestern United States The Precambrian geochronology of the southwestern United States is in an early stage of systematic study. Until recently, the only basis of correlation was through inconclusive field relationships. However, with the increased use of isotopic age dating, new data are becoming available for correlating regional and local events. As yet, there is no undisputed evidence of ages greater than 1.8 billion years (by) old in the southwestern United States. However, most geologists who have studied the region agree that volcanism and marine sedimentation of predominately eugeosynclinal facies took place in a northeasterly trending geosyn-cline prior to 1.7 by."' Because of insufficient evidence for a pregeosynclinal continental crust, some researchers believe the geosyncline may have developed on oceanic crust.' However, sediments metamorphosed to 1.7 by-old felsic paragneisses in the Panamint Range, California," and southeastward into southern Nevada are believed to have had a nearby continental provenance. The three Precambrian disturbances that are recognized in the southwestern United States are 1.6 to 1.8 by, about 1.4 by, and about 1.1 by-old (Fig. 3). In addition to plutonism, these disturbances are characterized by predominately lower-grade metamorphism. In this report, lower-grade metamorphic rocks include argillite, phyllite, slate, mica schist, and gneiss with relic sedimentary textures. Higher-grade metamorphic rocks, in this report, are recrystallized beyond megascopic recognition of the original rock type. Principal